Human Resources as Social Assets in Sustainable Tourism: Evaluating Impacts through Social Return on Investment (SROI) - Dinis Cahyaningrum; Tifani Dame Hasany; Zefanya Andryan Girsang; Dhanny Safitri; Khairul Mujahidi (West Science Business and Management, 2025)
Tourism is widely recognized as a significant driver of economic growth and employment; however, the role of human resources is often narrowly framed in economic terms, with limited recognition of their broader social contributions. This study explores human resources as social assets in sustainable tourism by integrating the concepts of social capital, community-based tourism (CBT), and the Social Return on Investment (SROI) framework. Using a descriptive qualitative approach through a structured literature review, the study examines how education, training, and community participation function as strategic mechanisms to strengthen local capacities and generate multidimensional value for tourism destinations. The analysis highlights how human resource development enhances not only technical competencies and service quality but also social cohesion, trust, and collective action within host communities. Findings indicate that investment in human resources contributes not only to improved service quality and economic gains but also to stronger community cohesion, cultural preservation, empowerment of local actors, and inclusive development processes. The application of the SROI framework provides a systematic way to capture and measure these broader social, cultural, and economic impacts that are often overlooked in conventional tourism evaluations. This study emphasizes that people-centered investment strategies are fundamental to achieving long-term sustainability in tourism development. The study concludes that human resources must be positioned as catalysts for both social and economic value creation, with important implications for tourism policy, destination governance, and community-based development practices.